2011
DOI: 10.1371/journal.pone.0021325
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 1 (PP1) Is a Post-Translational Regulator of the Mammalian Circadian Clock

Abstract: Circadian clocks coordinate the timing of important biological processes. Interconnected transcriptional and post-translational feedback loops based on a set of clock genes generate and maintain these rhythms with a period of about 24 hours. Many clock proteins undergo circadian cycles of post-translational modifications. Among these modifications, protein phosphorylation plays an important role in regulating activity, stability and intracellular localization of clock components. Several protein kinases were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 64 publications
2
36
0
Order By: Relevance
“…However, if CK1δ/ε activity is disrupted, PER phosphorylation slows down, resulting in a slower oscillator (27,54,55). While our work was under review, Schmutz et al (39) showed that inhibition of PP1 activity slightly lengthened the period of bioluminescence and behavioral rhythms. The difference in the effect of PP1 inhibition may be due to different levels of inhibition and/or different methods of inhibition.…”
Section: Discussionmentioning
confidence: 70%
“…However, if CK1δ/ε activity is disrupted, PER phosphorylation slows down, resulting in a slower oscillator (27,54,55). While our work was under review, Schmutz et al (39) showed that inhibition of PP1 activity slightly lengthened the period of bioluminescence and behavioral rhythms. The difference in the effect of PP1 inhibition may be due to different levels of inhibition and/or different methods of inhibition.…”
Section: Discussionmentioning
confidence: 70%
“…The significant suppression of Pgc1α and Ppara expression may likely result in decreased levels of the PPARα/PGC1α transcriptional complex with nuclear receptors, which may consequently affect the activity of downstream genes regulating fatty acid uptake and oxidation in the liver of SHR maintained under RF. The other metabolism-relevant gene expression profiles in the liver did not differ between the two strains, namely that of Pparg (critical regulator of adipogenesis and osteogenesis [62,63]), Hdac3 (histone deacetylase integrating metabolic and circadian regulation [64,65]), Hif1a (the alpha subunit of the hypoxia inducible factor regulating homeostatic response to hypoxia [66]) and Ppp1r3c (a subunit of protein phosphatase 1 and major metabolic regulator linked to the circadian clock [67,68]). Thus, the data suggest that RF impacts the metabolic state in the liver of SHR differently than in Wistar rats, with the most obvious difference in the suppression of Pgc1α and Ppara expression and the imposition of a low-amplitude rhythmicity in Ppara and Prkab2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…2, state 2 to state 1). Inhibition of PPP1 in mouse suprachiasmatic nuclei lengthens the free-running period and alters light induced phase shifts 53 . PPP5 also regulates the circadian clock in culture by preventing autophosphorylation of CKI (ref.…”
Section: Multiple Modifications Antagonizing Per Degradationmentioning
confidence: 99%